Development of a risk mapping along a railway - Gobbi, Felipe; Pereira, Alvaro; Denardin, Bruno; Madrid, Fabiano; Liboreiro, Karine; Coelho, Adoniran (Soils & rocks, 2023)
The Ramal Trem Turístico (RTT), a 17 km long railway between Ouro Preto and Mariana, a centenary line, currently in operation as a tourist attraction with historical importance. The railroad was built along a steep region, with hundreds of slopes, and eventually slope instabilities compromised the tour. In linear infrastructure projects, a risk assessment is an important tool for risk management, mapping it is the first step. After slope instabilities in 2019, a risk map was elaborated early 2021 for RTT. Risk is obtained by multiplying the probability of a certain event to occur by its consequences. Define its value in a quantitative way demands geotechnical investigation, for precise failure probability. Regardless of its importance, its determination needs high resources, specially for linear infrastructure in a region with heterogeneous geology and pedology. Therefore, for the risk mapping of the RTT, a semi-empirical methodology was adopted, based on the Rockfall Hazard Rating System (RHRS), originally developed for rocky slopes, and adapted for the registration of slopes in soil and in landfill. The aim of the method is to register a series of slope characteristics to be assigned a specific score, framing the slopes within pre-defined risk classes. This methodology was applied to this 17 km railway and identified 286 slopes. In January 2022 extreme rainfall triggered slopes instabilities at RTT. A critical analysis of this event shows a satisfactory result for the applied methodology. Risk mapping is an important tool for risk management, helping to prioritize investments in mitigation measures.